SIDEROPHORE PRODUCTION OF THE RHIZOBACTERIA ISOLATED FROM LOCAL “KAMBA” RICE PLANTS, POSO REGENCY IN CENTRAL SULAWESI - Sri Sudewi; Baharuddin Patandjengi; Ambo Ala; Muh Farid BDR; Abdul Rahim Saleh; Ratnawati Ratnawati (Agric, 2022)
Rhizobacteria isolated from plant roots have the ability to produce siderophore compounds. These compounds play a role in inhibiting the growth of pathogens by binding to iron (Fe3+) which is needed by pathogens in their development. This research was aimed to find out the siderophore-producing bacteria isolated from local Kamba rice plants and their potential as biocontrol agents. Among the 28 isolates that were successfully isolated from the Kamba local rice rhizosphere, 10 isolates had the potential to produce siderophores with different morphological characters. The test was carried out to see the bacterial isolates capabilities to produce siderophores from two types of siderophores namely catechol and salicylate types. For the catechol type, the highest concentration of siderophore was found in the KBA8 bacterial isolate with 10.990 mg L-1, while the lowest was in the KBA1 bacterial isolate with only 5.876 mg L-1. The salicylate type siderophore with the highest concentration produced 9.493 mg L-1 was from the RKGU15 isolate and the lowest was found in KBU14 isolate which produced only 2.994 mg L-1. The isolates included in the Gram-positive group were 4 isolates while the Gram- negative group were 6 isolates and 90% isolates were able to produce the enzyme catalase. The results of this study indicate that all bacterial isolates can produce siderophores so that they have the potential as biocontrol agents to support environmentally friendly and sustainable agriculture.